PERANCANGAN ECONOMICAL BALANCE DONGKRAK ULIR ELEKTRIK DWI HASTA - Muhammad Dimas Ferdiansyah; Sukendro Sasongko (Otopro, 2023)
The Dwi Hasta lifting crew jack is a tool that assist the car maintenance mechanician. It tool support the car at an elevationfor the maintenance working and lay it down after the mechanician done. The objective of study is to obtain the cost of themanufacturing from production stage to selling. In which, it device is for assisting the mechanician repaired a car. Manufacture system would obtain economic values and production time at one unit. The investigation is started from design, and to the manufacturing system. Regards to the planning of the manufacturing, the production cost, the selling cost, and time of refund are obtained at the cost calculation. The money refund is the production cost will get after selling. The experiment method is conducted at operating process chart (OPC), manufacturing lead time (MLT), production time, production flow, production capacity and break event point (Q). The experiment results showed economic value from raw material to one-unit machine. MLT is of about 53,83 hours. Production time performs is for 346,7 min. Production capacity is 6 units per month. Break Event Point (Q) will be started after 3 months. The profit taking back is Rp 6.181. 964. Money will be payback after 3 month